Second-generation DNA-templated macrocycle libraries for the discovery of bioactive small molecules - Usanov, Dmitry L.; Chan, Alix I.; Maianti, Juan Pablo; Liu, David R. (Nature chemistry, 2018)
DNA-encoded libraries have emerged as a widely used resource for the discovery of bioactive small molecules, and offer substantial advantages compared with conventional small-molecule libraries. Here, we have developed and streamlined multiple fundamental aspects of DNA-encoded and DNA-templated library synthesis methodology, including computational identification and experimental validation of a 20 × 20 × 20 × 80 set of orthogonal codons, chemical and computational tools for enhancing the structural diversity and drug-likeness of library members, a highly efficient polymerase-mediated template library assembly strategy, and library isolation and purification methods. We have integrated these improved methods to produce a second-generation DNA-templated library of 256,000 small-molecule macrocycles with improved drug-like physical properties. In vitro selection of this library for insulin-degrading enzyme affinity resulted in novel insulin-degrading enzyme inhibitors, including one of unusual potency and novel macrocycle stereochemistry (IC 50 = 40 nM). Collectively, these developments enable DNA-templated small-molecule libraries to serve as more powerful, accessible, streamlined and cost-effective tools for bioactive small-molecule discovery. A second-generation DNA-templated library of 256,000 small-molecule macrocycles has been developed. The improved method was created by streamlining and integrating multiple aspects of DNA-encoded and DNA-templated library synthesis methodology. In vitro selection of the macrocycle library against insulin-degrading enzyme enabled the discovery of potent inhibitors.